Cardiovascular progenitor cells and tissue plasticity are reduced in a myocardium affected by Becker muscular dystrophy - Pesl, Martin; Jelinkova, Sarka; Caluori, Guido; Holicka, Maria; Krejci, Jan; Nemec, Petr; Kohutova, Aneta; Zampachova, Vita; Dvorak, Petr; Rotrekl, Vladimir (Orphanet journal of rare diseases, 2020)
UNLABELLED: We describe the association of Becker muscular dystrophy (BMD) derived heart failure with the impairment of tissue homeostasis and remodeling capabilities of the affected heart tissue. We report that BMD heart failure is associated with a significantly decreased number of cardiovascular progenitor cells, reduced cardiac fibroblast migration, and ex vivo survival. BACKGROUND: Becker muscular dystrophy belongs to a class of genetically inherited dystrophin deficiencies. It affects male patients and results in progressive skeletal muscle degeneration and dilated cardiomyopathy leading to heart failure. It is a relatively mild form of dystrophin deficiency, which allows patients to be on a heart transplant list. In this unique situation, the explanted heart is a rare opportunity to study the degenerative process of dystrophin-deficient cardiac tissue. Heart tissue was excised, dissociated, and analyzed. The fractional content of c-kit+/CD45- cardiovascular progenitor cells (CVPCs) and cardiac fibroblast migration were compared to control samples of atrial tissue. Control tissue was obtained from the hearts of healthy organ donor's during heart transplantation procedures. RESULTS: We report significantly decreased CVPCs (c-kit+/CD45-) throughout the heart tissue of a BMD patient, and reduced numbers of phase-bright cells presenting c-kit positivity in the dystrophin-deficient cultured explants. In addition, ex vivo CVPCs survival and cardiac fibroblasts migration were significantly reduced, suggesting reduced homeostatic support and irreversible tissue remodeling. CONCLUSIONS: Our findings associate genetically derived heart failure in a dystrophin-deficient patient with decreased c-kit+/CD45- CVPCs and their resilience, possibly hinting at a lack of cardioprotective capability and/or reduced homeostatic support. This also correlates with reduced plasticity of the explanted cardiac tissue, related to the process of irreversible remodeling in the BMD patient's heart.
Keywords: Cardiomyopathy; Dystrophin; Cardiovascular progenitor cells; Male; C-kit; mužské pohlaví; Becker muscular dystrophy; Heart failure; myokard; Humans; Cardiomyopathy, Dilated; dilatační kardiomyopatie; Myocardium; Duchennova muskulární dystrofie; Stem Cells; dystrofin; kmenové buňky; lidé; Muscular Dystrophy, Duchenne